(untitled) (gjstudies, 2024)
This research investigates the relationship between strategic cost control practicesand organizational competitive positioning, proposing a novel framework that integrates principles from cybernetics, complex adaptive systems, and behavioral economics into traditional management accounting. While conventional studies treat costcontrol as a reactive, operational function, this paper re-conceptualizes it as a dynamic,anticipatory system capable of shaping competitive advantage. We develop a methodology based on agent-based modeling and simulation to analyze how different cost control strategies—categorized as adaptive, predictive, and transformative—influence anorganization’s ability to secure and maintain competitive positions in volatile markets.Our simulation environment models a competitive landscape of 50 heterogeneous firmsover 1,000 operational cycles, incorporating stochastic demand shocks, technologicaldisruptions, and strategic interactions. The results demonstrate that transformativecost control practices, characterized by real-time feedback loops, decentralized decisionrights, and investment in strategic cost intelligence, correlate strongly with superior andmore resilient competitive positioning, particularly in high-velocity industries. Conversely, rigid, accounting-centric control systems are associated with positional erosionunder conditions of turbulence. The study’s primary contribution is the Strategic CostPositioning (SCP) framework, which provides a diagnostic tool for managers to aligncost management with strategic intent. This research bridges a significant gap betweenstrategic management theory and cost accounting practice, offering a forward-lookingperspective essential for navigating contemporary economic uncertainties.